DISTRIBUCIÓN ESPACIAL Y FLUCTUACIÓN POBLACIONAL DE PHYLLOCOPTRUTA OLEIVORA (ASHMEAD) (ACARI: ERIOPHYIDAE) EN CÍTRICOS DE GÜEMEZ, TAMAULIPAS - Landeros, Jeronimo; Balderas, Juan; Badii, Mohammad H; Sánchez, Victor M.; Guerrero, Eugenio; Flores, Adriana E. (Instituto de Ecología, A.C., 2003)
The present investigation was accomplished in the county of Güemez, Tamaulipas, Mexico during the period june of 1998 to October of 1999. The objectives were to evaluate the spatial distribution and the population fluctuation of the citrus rust mite Phyllocoptruta oleivora (Ashmead). This investigation was conducted on 10 orange trees of the variety Valencia selected at random in an area of a hectarea. Each tree was divided into 7 sampling areas. Samples were taken every 14 days, using the leaf as the sample unit and counting the number of mites present on both sides of the leaves. A total of 10 leaves were observed in each of 7 sections, making a total of 70 leaves for each tree and 700 for each sampling date. Using the mean densities and the variance obtained in each sampling, a statistical analysis was conducted to determine the spatial distribution of the mite in the area study. Eight indexes were used to determine the spatial distribution. The index values of Lexis , Charlier, David & Moore, Green and the dispersion parameter (K) of negative binomial indicated a clumped distribution for this mite over all 16 sampling dates. However the values of Morisita, Iwao, and Taylor´s power law showed random distribution in two, two, and three sampling dates, respectively. In all samples, the highest mite densities were found in the middle tree stratum (with higher aggregation toward last section of tree) followed by bottom and top strata, respectively. Population peaks were found during march 27 th and september 25 th. The dependent variable used to estimate the populate on fluctuation was the mean density of the mites in each sampling date. The independent variables were: temperature, relative humidity and precipitation. A detected positive correlation between the mean density of the mites and temperatures was observed.